PENTINGNYA ETIKA BERBAHASA SEBAGAI UPAYA PENCEGAHAN KASUS KEJAHATAN BERBAHASA DI MEDIA DIGITAL - Taufiq, Muhammad; Maliki, Dwiki Osa; Maldini, Andry Syva; Ekamartha, Ken Narendra; Saputra, Kurniawan Nur Cahya; Ahmad, Sayyid Haqqu; Pillardien, Esa; Sholihatin, Endang (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Language crime cases in digital media are increasingly becoming a serious concern in modern society. In today's digital age, social media platforms and online communication have become important means of information exchange and social interaction. However, the development of this technology also has a negative impact, where violations of language ethics are becoming increasingly common. Therefore, this paper aims to find out the form of language crime on digital media in Indonesia and know good language ethics to prevent cases of language crime on digital media in Indonesia. This research method uses qualitative research methods with data collection techniques through observation. Analysis of the literature reveals that language crimes on digital media in Indonesia include the spread of hoaxes, online harassment and fraud, personal data hijacking, cyberbullying, and hate speech. To prevent that language ethics plays its main key role, language ethics involves the use of language that is respectful, honest, responsible, and does not harm others. By practicing good language ethics, individuals can contribute to creating a safe, inclusive, and dignified digital environment